2011
DOI: 10.1039/c0cc05748g
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of latent fingermarks on non-porous surfaces using anti-l-amino acidantibodies conjugated to gold nanoparticles

Abstract: Enantioselective anti-L-amino acid antibodies conjugated to gold nanoparticles are shown to facilitate the detection of latent fingermarks by interacting with amino acids present in friction ridge secretions. This antibody-based system is particularly effective for the enhancement of aged and dried fingermarks on non-porous surfaces, an area unexploited by current techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 16 publications
0
48
0
2
Order By: Relevance
“…Spindler et al [32] have shown that gold NPs conjugated with anti-L-amino acid antibodies can visualize LFPs on non-porous surfaces. Using dermcidin as the antigen of interest, van Dam et al [70] investigated the compatibility of immunolabeling with two commonly used fingerprint visualization techniques: magnetic powdering and ninhydrin staining.…”
Section: Immunological Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Spindler et al [32] have shown that gold NPs conjugated with anti-L-amino acid antibodies can visualize LFPs on non-porous surfaces. Using dermcidin as the antigen of interest, van Dam et al [70] investigated the compatibility of immunolabeling with two commonly used fingerprint visualization techniques: magnetic powdering and ninhydrin staining.…”
Section: Immunological Techniquesmentioning
confidence: 99%
“…(i) The improvement of enhancement techniques for exploiting more portable and efficient manners; and (ii) the development of component recognition for elucidating advanced knowledge about fingerprint composition, such as gender [31], diet [32], the presence of human metabolites with diagnostic values [33] and the evidence of contact with explosives or illicit drugs [34].…”
Section: Introductionmentioning
confidence: 99%
“…In work by Spindler et al 36 , the use of antibodies conjugated to gold nanoparticles was examined as an immunogenic technique targeting amino acids within latent fingermarks. In this work, anti-L-amino acid antibodies were conjugated to 16 nm diameter gold nanoparticles by either direct electrostatic adsorption or through covalent amide bond formation to a thioether 36 .…”
Section: Recent and Current Research Using Immunogenic Techniquesmentioning
confidence: 99%
“…In this work, anti-L-amino acid antibodies were conjugated to 16 nm diameter gold nanoparticles by either direct electrostatic adsorption or through covalent amide bond formation to a thioether 36 . These conjugates were dispersed in a water-acetone mixture before being applied to latent fingermarks placed on non-porous substrates.…”
Section: Recent and Current Research Using Immunogenic Techniquesmentioning
confidence: 99%
“…Dozens of detection techniques have been investigated and optimised to date [1,2]. Emerging technologies such as nanotechnology [3] and immunodetection techniques [4,5] have also been applied in the field, leading to the discovery of new, highly promising detection methods. But, despite the numerous available options and current endeavours to find increasingly more effective methods, a general lack of sensitivity and specificity has been noted.…”
Section: Introductionmentioning
confidence: 99%